Evaluating the Factors Affecting the Occurrence of Symptomatic COVID-19 Illness after Vaccination - Zehra, Tehzeeb; Aamir, Rahila; Batool, Uzma; Sultan Baig, Wajahat; Bacha, Faisal; Riaz, Nimra (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Vaccination against COVID-19 illness is mainstay of undertaking the pandemic. However, it has been frequently observed that many patients developed COVID-19 illness after vaccination. Aim: To find out the factors other than the “mere chance” affecting the development of COVID-19 illness after vaccination so to identify high risk population and to suggest modify their vaccinations accordingly. Study design: Descriptive, retrospective cohort study Place and duration of study: Falahee Foundation Clinics of Shifa International Hospital, Islamabad from 1st February 2021 to 31st July 2021. Methodology: Sixty health care workers (HCW) who got vaccinated were enrolled. Results: 34 (58.6%) were male and 26 (41.4%) were females with mean age of 42±8.3 years. Twenty (33.3%) HCWs developed post vaccination symptoms, 12 of them got their COVID-19 PCR done. Seven (58.33%) had positive PCR and 5 (41.66%)had negative PCR. Female gender and co-morbid conditions affected the post vaccination symptoms and positivity of PCR significantly. Conclusion: Female gender, hypothyroidism, hypertension and celiac disease patients proved high risk for vaccination in our limited cohort. So co-morbid condition need consideration regarding further inquiry and necessary vaccination modifications.